2017
DOI: 10.1016/j.snb.2017.05.111
|View full text |Cite
|
Sign up to set email alerts
|

Continuous noninvasive monitoring of cell growth in disposable bioreactors

Abstract: To ensure high quality output of biotechnological processes, relevant process parameters need to be monitored. As bioprocesses are increasingly executed in single use bioreactors, there is an increasing demand for new sensors applicable to these processes. In this work, we investigate different approaches for continuous non-invasive cell growth monitoring, especially for single use bioreactor applications. Therefore, the permittivity of the cell culture is used as a measure for the biomass. In a first step, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…Biomass can be quantified indirectly by off-gas analysis to measure respiration [ 2 , 3 ], 2D fluorescence spectroscopy to calculate the NAD(P)H content [ 4 , 5 ], biocalorimetry to monitor metabolic heat [ 6 ], or a combination of process data using soft sensors [ 7 ]. Direct methods include cell counting by in situ microscopy [ 8 ], near-infrared (NIR) spectroscopy [ 9 ], online optical density measurements [ 3 , 10 , 11 , 12 ] and dielectric spectroscopy [ 6 , 13 , 14 , 15 ]. Regardless of the chosen strategy, online biomass monitoring systems must meet several requirements [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass can be quantified indirectly by off-gas analysis to measure respiration [ 2 , 3 ], 2D fluorescence spectroscopy to calculate the NAD(P)H content [ 4 , 5 ], biocalorimetry to monitor metabolic heat [ 6 ], or a combination of process data using soft sensors [ 7 ]. Direct methods include cell counting by in situ microscopy [ 8 ], near-infrared (NIR) spectroscopy [ 9 ], online optical density measurements [ 3 , 10 , 11 , 12 ] and dielectric spectroscopy [ 6 , 13 , 14 , 15 ]. Regardless of the chosen strategy, online biomass monitoring systems must meet several requirements [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows a linear dependency with a coefficient of determination R 2 = 0.96 between Us' and the optical density of the culture medium up to an optical density of OD = 4. Compared to the results shown in [5], the measured sensitivity is significantly increased using the optimal measuring frequency of 108.4 kHz. …”
Section: Resultsmentioning
confidence: 58%
“…Therefore, the measuring voltage Us equals the induced voltage in Ls2. In [5], it is shown that the real part of the measuring voltage Us' depends on the polarizability of the medium (ε r ') and the imaginary part of the measuring voltage Us'' depends on the dielectric losses (εr'') and the conductivity (κ). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations